Size‐Dependent Inhibition of Sperm Motility by Copper Particles as a Path toward Male Contraception. Issue 7 (28th April 2022) - Chattopadhyay, Purnesh; Magdanz, Veronika; Hernández-Meliá, María; Borchert, Konstantin B. L.; Schwarz, Dana; Simmchen, Juliane
Abstract : Effective inhibition of sperm motility using a spermicide can be a promising approach in developing non‐invasive male contraceptive agents. Copper is known to have contraceptive properties and has been used clinically for decades as intrauterine contraceptive devices (IUDs) for contraception in females. Beyond that, the spermicidal use of copper is not explored much further, even though its use can also subdue the harmful effects caused by the hormonal female contraceptive agents on the environment. Herein, the size, concentration, and time‐dependent in vitro inhibition of bovine spermatozoa by copper microparticles are studied. The effectivity in inhibiting sperm motility is correlated with the amount of Cu 2+ ions released by the particles during incubation. The copper particles cause direct suppression of sperm motility and viability upon incubation and thereby show potential as sperm‐inhibiting, hormone‐free candidate for male contraception. In addition, biocompatibility tests using a cervical cell line help optimizing the size and concentration of the copper particles for the best spermicidal action while avoiding toxicity to the surrounding tissue. Abstract : Copper microparticles are very effective in inhibiting sperm motility and viability. This inhibition is influenced by various experimental factors as shown. The inhibition effectivity increases with decrease in particle size, with increase in particle concentration and with increasing incubation time.